Normalization and variant assessment methods in selection of road alignment variants – case study - Gardziejczyk, Wladyslaw; Zabicki, Piotr (Journal of Civil Engineering and Management, 2017)
The choice of the most beneficial road alignment variant is a multicriteria issue, based on transport, economic, social and environmental criteria. The criteria chosen for a multicriteria analysis can be expressed through measurable or immeasurable parameters. In order to compare and assess the variants it is necessary to normalize the criteria, which means a rescaling of their value, so that the criteria values fall into a specific range. The main aim of normalization is to assign an identical weight to each criterion in relation to other criteria. This article presents a review of the influence of criteria normalization methods and the variant assessment methods on the choice of the most beneficial road alignment variant on the example of the bypass of the town of Księżyno, which is a stretch of Regional Road 678 near Bialystok. Four variants of road alignment were compared and their ranking was created using six assessment methods. It was proven that the choices of the criteria normalization method as well as the variant assessment method both have significant influence on the result of the multicriteria analysis in the decision-making process of selecting the road alignment.